Il trattamento delle psicosi in una comunità terapeutica - Madrucci, Matteo; Cardamone, Giuseppe (Il sogno della farfalla, 2016)
This article deals with the theme of treating psychosis within a therapeutic community of the Tuscan public health system. The importance of a community-based treatment in facing serious psychotic pathologies is highlighted. We are told of an attempt to move away from a predominantly rehabilitative approach (where a series of interventions aim to help the patient learn more socially evolved and acceptable behavior) to an approach mainly based on psychotherapy.